Association of sodium intake with incident asthma and the modifying role of potassium: insights from a prospective study - Wufeng Huang; Daniel Nyarko Hukportie; Jing Kang; Wen Li; Laiyu Liu; Fu-Rong Li; Wei Chi (BMC Public Health, 2026)
Abstract Background Emerging evidence suggests that high dietary salt intake may contribute to the development of immune-mediated diseases, including asthma. However, the relationship between salt consumption and the risk of adult-onset asthma, as well as how it may be influenced by other dietary electrolytes, remains unclear. This study aimed to clarify the association between salt intake and asthma risk, with particular attention to the potential interaction with urinary potassium levels. Methods We conducted a prospective cohort study of 373,647 adults from the UK Biobank who were free of asthma at baseline. Salt intake was evaluated using two complementary approaches: a subjective measure based on the self-reported frequency of adding salt to foods, and an objective estimate of 24-h sodium excretion derived from spot urine samples. Urinary potassium levels were also measured from spot urine samples and used as an indicator of potassium status. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for the association between salt intake and asthma incidence, adjusting for multiple potential confounding factors, and to assess potential effect modification by spot urinary potassium concentrations. Results Over a median follow-up period of 15.4 years, we documented 10,511 incident asthma cases. Compared with those who never or rarely added salt, participants who reported always adding salt had a 27% higher risk of asthma (HR 1.27, 95% CI 1.17–1.38). Each 1-g/day increase in estimated 24-h sodium excretion was associated with a 15% higher asthma risk in men and a 39% higher risk in women. Spline analyses further showed a progressively increasing asthma risk with higher estimated 24-h sodium excretion, with a notably steeper gradient at lower spot urinary potassium concentrations and a modest attenuation at higher levels, supporting a potential sodium–potassium interaction in relation to asthma risk ( P for interaction < 0.05). Conclusion In this large cohort study, both self-reported high salt-adding habits and higher estimated 24-h sodium excretion were associated with an increased incidence of asthma. Notably, higher spot urinary potassium concentrations appeared to attenuate the adverse effects of high sodium on asthma risk, suggesting that a combined dietary strategy of reducing salt intake while maintaining adequate potassium may help lower the risk of adult-onset asthma.